The Impacts Analysis of Creative-Products Export on the Economy - Sukma, Muhammad; Hartono, Djoni; Prihawantoro, Socia (Universitas Negeri Semarang, 2018)
The increase of export value of creative industry in the middle of the declining export value of Indonesia's leading commodities during the period of 2011 to 2015 indicates that the creative industry potentially encourages the economic growth in Indonesia. This study aims to observe the linkages of creative industries, both forward and backward linkages, with other sectors in the economy. This study also examines the impacts of the increasing export on the fashion and craft sectors, as the two largest contributors to the export of creative industries, towards the Indonesian economy. Applying the Input-Output approach, the influence of the export of fashion and craft sectors towards the Indonesian economy is seen from the multiplier effects on the increasing value added, community income and labor absorption. The results show that fashion exports increased the national value added by 0.06%; community income 0.06% and employment 0.11%. Similarly, craft exports increased the national value added by 0.05%; income by 0.05% and employment by 0.11%. The largest increase is in the labor absorption; this is because the fashion and craft sectors are labor intensive sectors.